ACETYLATION OF MICROFIBRILLATED CELLULOSE BY REACTION WITH ACETIC ANHYDRIDE CATALYZED BY N-BROMOSUCCINIMIDE - Giang, Le Duc; Cuong, Cao Xuan; Hoa, Ta Phuong; Loc, Thach Thi (Vietnam Journal of Science and Technology, 2015)
Cellulose acetate (DS=2.3) was prepared by reacting microfibrillated cellulose (MFC) with acetic anhydride using N-bromosuccinimide as a catalyst. The reaction was conducted using dimethyl sulfoxide as the solvent, at 600C for 120 minutes. Chemical structure of product was determined by IR, 1H-NMR and 13C-NMR.The phase structure and the degree of crystallinity of the sample was deduced from the powder X-ray diffraction (PXRD). The thermal stability was investigated by thermal gravimetric analysis (TGA). The results showed that MFC acetate had characteristic of cellulose type I structure with the degree of crystallinity of 50.45%  and the decomposition of the sample took place in the temperature range of 240-420oC.